Indonesia-Singapore Realignment Agreement 2022: Quo Vadis Indonesia’s Air Sovereignty, Defense and Security? - Putro, Yaries Mahardika; Felix Alexander Kurniawan; Britney Nathania Lielien Putrajaya; Sherren Laurencia (Prophetic Law Review, 2024)
In 2022, after a 76-year wait, Indonesia finally witnessed the fruition of the Agreement on the Realignment of the Jakarta Flight Information Region and the Singapore Flight Information Region. However, President Jokowi's statements created ambiguity, leading to widespread misconceptions that Indonesia's airspace sovereignty over the Riau Islands and Natuna was only established during his tenure through the FIR agreement in 2022. This research aims to evaluate the impact of the airspace adjustment agreement ratified in 2022 between Indonesia and Singapore on Indonesia's air sovereignty and explore potential legal remedies. The research methodology encompasses normative legal analysis, including statutory, conceptual, and historical approaches. From a sovereignty standpoint, the FIR agreement in 2022 has implications for violating Indonesia's airspace sovereignty. Past sovereignty violations resulting from the 1995 FIR agreement could resurface post-2022. Civil-military cooperation in air traffic management is needed to restore Indonesia's compromised airspace sovereignty fully. Moreover, the agreement's 25-year duration conflicts with Law Number 1 of 2009 on Aviation. To rectify this, a crucial legal step involves establishing a takeover agreement, rather than a mere realignment, of the FIR from Singapore, followed by ratification through legislation. The public can engage in a judicial review of Presidential Regulation No. 109 of 2022 at the Supreme Court. Additionally, it is imperative to advocate for creating an Airspace Management Bill to address these complex airspace sovereignty concerns.